Fibrosis in Arrhythmogenic Cardiomyopathy: The Phantom Thread in the Fibro-Adipose Tissue - Maione, Angela Serena; Pilato, Chiara Assunta; Casella, Michela; Gasperetti, Alessio; Stadiotti, Ilaria; Pompilio, Giulio; Sommariva, Elena (Frontiers in Physiology, 2020)
In addition to the arrhythmic features, Arrhythmogenic Cardiomyopathy (ACM) hearts show a progressive loss of myocardium with fibrous or fibro-fatty substitution. During the last few decades, different clinical aspects of ACM have been well investigated but still little it is known about the molecular mechanisms that underlie ACM pathogenesis, leading to these phenotypes. In about 50% ACM patients, a genetic mutation, predominantly in genes that encode for desmosomal proteins, has been identified. However, the mutation-associated mechanisms, causing the observed cardiac phenotype it is not always clear. Until now, the attention has been principally focused on the study of molecular mechanisms that lead to a prominent myocardium adipose substitution, an uncommon marker for a cardiac disease, thus often recognized as hallmark of ACM. Nonetheless, based on Task Force Criteria for the diagnosis of ACM, cardiomyocytes death associated with fibrous replacement of the ventricular free wall must be considered the main tissue hallmark in ACM patients. For this reason, it urges to investigate ACM cardiac fibrosis. In this review, we give an overview on the cellular effectors, possible triggers and molecular mechanisms that could be responsible for the ventricular fibrotic remodeling in ACM patients.